Faith-Based Schools in Latin America : Case Studies on Fe Y Alegria - Parra Osorio, Juan Carlos (Washington, DC: World Bank, 2013)
Many observers consider Fe y Alegría a successful organization, but very few rigorous evaluations have been conducted. This volume is devoted to an assessment of the performance and selected aspects of the management and pedagogical practices of Fe y Alegría, a federation of Jesuit schools serving approximately one million children in 20 countries, mostly in Latin America. The available quantitative evidence suggests that the federation’s schools often do reach the poor, and that students in Fe y Alegría schools tend to perform as well on test scores, if not slightly better than comparable students in other schools. Qualitative data and case studies suggest that the factors that lead to good performance are complex and related not only to the types of “inputs” or resources used by the schools in the education process, but also to the management of these resources, and the ability to implement and test innovative programs. Other factors that support this argument include the capacity and flexibility to implement and test innovative programs that take into account the local realities. This volume will be of interest to researchers, policy makers and practitioners working in service provision through public-private partnerships and especially by faith-based organizations.